Carbothermic reduction of Zambian sulphide concentrates in presence of lime. (1st September 2013) - Hara, Y. S. R.; Jha, A.
Abstract : The investigation focuses on an alternative route to metallic phase extraction from complex Zambian copper-cobalt sulphide mineral concentrates, derived from the Copperbelt region. In the context of developing a novel process route for metal extraction without sulphur dioxide emission and slag waste generation, we have studied the reduction of copper-cobalt sulphide concentrates via carbothermic reduction in the presence of lime by following the equilibrium: MS+CaO+C = M+CaS+CO(g), where M represents the metallic copper, cobalt and iron. The effects of stoichiometric ratios of MS/CaO and MS/C were analysed over a range of temperature between 1073 and 1273 K. The reaction mechanism was analysed by identifying the phases formed, which were characterised by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) techniques. The metallic phase analysis confirmed the presence of 85-97 wt-% alloy, which formed as a result of carbothermic reduction. The extent of metallization was analysed by plotting percentage reduction (%R) for each reaction against time ( t ), from which three different regions of overall reaction were determined. Based on this approach, the overall reaction mechanism is discussed.